Health, Quality of Life and Population Density: A Preliminary Study on "Contextualized" Quality of Life - Fassio, Omar; Rollero, Chiara; De Piccoli, Norma (Social indicators research, 2013)
Quality of life concerns individual (physical and psychological health), interpersonal (social relationships) and contextual (environment) aspects, which are both subjective and objective. In considering contextual characteristics, empirical findings have demonstrated that people's relation to their living environment is a key issue for their well-being. However, until now literature has paid little attention to population density as an element affecting quality of life. The present study aimed at assessing the predictive role of population density on the several domains of quality of life, along with socio-demographic characteristics and physical diseases. Participants were 344 subjects living in the Northern Italy area. A questionnaire with WHO Quality of Life Brief Scale, a checklist of chronic diseases and a socio-demographic form was used to collect data. Results showed that population density influences psychological, relational and environmental quality of life. Theoretical and policy implications are discussed.